Clinical and viro-immunological correlates of HIV associated neurocognitive disorders (HAND) in a cohort of antiretroviral-naïve HIV-infected patients. (14th January 2017) - Bai, Francesca; Iannuzzi, Francesca; Merlini, Esther; Borghi, Lidia; Tincati, Camilla; Trunfio, Mattia; Bini, Teresa; Monforte, Antonella d'Arminio; Marchetti, Giulia
Abstract : The multifactorial pathogenesis of HIV-associated neurocognitive disorders may explain the inconsistent association between neurocognitive impairment and cerebrospinal fluid (CSF) HIV RNA. Clinical and viro-immunological (CSF and plasma HIV RNA, CSF/plasma HIV RNA ratio, circulating T-cell phenotypes) parameters were investigated in 155 HIV-infected, antiretroviral-naïve, asymptomatic study participants undergoing a neuropsychological evaluation. HIV associated neurocognitive disorders (HAND) was independently associated with AIDS events and a CSF/plasma ratio of at least one, after adjustment for CD4 + nadir of less than 200 cells/mmc, suggesting a role for active central nervous system (CNS) viral replication in the pathogenesis of neurocognitive impairment.